Implementation of the Implementation of Fun Learning Through Learning Video Media in Improving Indonesian Literacy - Yatra, I Ketut Adi Darma; Trisnayanti, Ni Putu Elya; Widiadnyani, Kadek; Tri Wahyunita, I Gusti Ayu Widya; Pramita, Putu Ayu; Dwi Wahyuni, I Gusti Ayu Winda (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
This study aims to evaluate the effectiveness of applying enjoyable learning through video media to improve Indonesian language literacy. The research method used is a mixed-method approach, combining quantitative data analysis from pre-tests and post-tests with qualitative data obtained through classroom observations, interviews with students and teachers, and the analysis of students' reflective journals. The results of the study show a significant improvement in Indonesian language literacy scores in the group of students who used video-based learning compared to the control group that used conventional teaching methods. The use of video media in learning increased Indonesian language literacy, with an average score improvement of 22.9 points (39.60%). Most students experienced an increase of more than 30%, demonstrating the effectiveness of this method in enhancing material comprehension. This improvement covers various aspects of literacy, including reading, writing, understanding, and interpreting texts. Overall, this study makes an important contribution to the development of technology-based learning methods and shows that video-based learning can be an effective tool for improving Indonesian language literacy. The findings are relevant for educators and policymakers in Indonesia, and they offer a new direction for developing educational practices in various other contexts.Penelitian ini bertujuan untuk mengevaluasi efektivitas penerapan pembelajaran yang menyenangkan melalui media video dalam meningkatkan literasi bahasa Indonesia. Metode penelitian yang digunakan adalah metode campuran, menggabungkan analisis data kuantitatif dari pre-test dan post-test dengan data kualitatif yang diperoleh melalui observasi kelas, wawancara dengan siswa dan guru, serta analisis jurnal reflektif siswa. Hasil penelitian menunjukkan adanya peningkatan signifikan pada skor literasi bahasa Indonesia di kelompok siswa yang menggunakan video pembelajaran dibandingkan dengan kelompok kontrol yang menggunakan metode pembelajaran konvensional Penggunaan media video dalam pembelajaran meningkatkan literasi Bahasa Indonesia siswa, dengan rata-rata skor meningkat 22.9 poin (39.60%). Sebagian besar siswa mengalami kenaikan lebih dari 30%, menunjukkan efektivitas metode ini dalam meningkatkan pemahaman materi. Peningkatan ini mencakup berbagai aspek literasi, termasuk kemampuan membaca, menulis, memahami, dan menginterpretasikan teks. Secara keseluruhan, penelitian ini memberikan kontribusi penting bagi pengembangan metode pembelajaran berbasis teknologi dan menunjukkan bahwa video pembelajaran dapat menjadi alat yang efektif untuk meningkatkan literasi bahasa Indonesia. Hasil penelitian ini relevan bagi pendidik dan pembuat kebijakan di Indonesia, serta menawarkan arah baru bagi pengembangan praktik pendidikan di berbagai konteks lainnya.